Integration of Social Emotional Learning (SEL) in Elementary School Curriculum: Strategies, Implementation, and Impact on Learning - Inggi Nurfauzia; Habibah Noor Fitriyah; Tri Wahyuni; Yeti Heryati; Dede Mardiah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, Jurusan Tarbiyah dan Keguruan, Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study aims to examine the role of emotional approaches in learning, identify strategies that are effectively applied by teachers, and assess their influence on students' social-emotional development and academic achievement. The results show that the implementation of Social Emotional Learning (SEL) is effective when it is flexibly integrated through explicit and integrated approaches, with success strongly influenced by teacher training, parental involvement, and local cultural appropriateness. SEL has been shown to increase self-regulation, empathy, learning motivation, and indirectly support the improvement of academic achievement. This research offers novelty through a comprehensive SEL implementation model by emphasizing the importance of a combination of continuous teacher training, structured play methods, integration of psychological safety, and valid mixed evaluations. These findings contribute to the development of adaptive, contextual, and sustainable learning strategies for primary education.